Aspartame Endowed ZnO-Based Self-Healing Solid Electrolyte Interface Film for Long-Cycling and Wide-Temperature Aqueous Zn-Ion Batteries - Shi, Yunyu; Liu, Yingkang; Chang, Ruirui; Zhang, Guilin; Rang, Yuqing; Xu, Zheng‑Long; Meng, Qi; Cao, Penghui; Zhou, Xiangyang; Tang, Jingjing; Yang, Juan (Nano-Micro Letters, 2025)
Metallic Zn anodes suffer from hydrogen evolution and dendritic deposition in aqueous electrolytes, resulting in low Coulombic efficiency and poor cyclic stability for aqueous Zn-ion batteries (AZIBs). Constructing stable solid electrolyte interphase (SEI) with strong affinity for Zn and exclusion of water corrosion of Zn metal anodes is a promising strategy to tackle these challenges. In this study, we develop a self-healing ZnO-based SEI film on the Zn electrode surface by employing an aspartame (APM) as a versatile electrolyte additive. The hydrophobic nature and strong Zn affinity of APM can facilitate the dynamic self-healing of ZnO-based SEI film during cyclic Zn plating/stripping process. Benefiting from the superior protection effect of self-healing ZnO-based SEI, the Zn║Cu cells possess an average coulombic efficiency more than 99.59% over 1,000 cycles even at a low current density of 1 mA cm−2 − 1 mAh cm−2. Furthermore, the Zn║NH4+-V2O5 full cells display a large specific capacity of 150 mAh g−1 and high cyclic stability with a capacity retention of 77.8% after 1,750 cycles. In addition, the Zn║Zn cell delivers high temperature adaptability at a wide-temperature range from − 5 to 40 °C even under a high DOD of 85.2%. The enhanced capability and durability originate from the self-healing SEI formation enabled by multifunctional APM additives mediating both corrosion suppression and interfacial stabilization. This work presents an inspired and straightforward approach to promote a dendrite-free and wide-temperature rechargeable AZIBs energy storage system. Highlights: 1 Aspartame additive in electrolyte enables the in situ formation of ZnO-based solid electrolyte interphase, enhancing Zn anode corrosion resistance and stability with excellent self-healing capabilities. 2 Zn║Zn symmetric cells with APM-modified electrolyte operate stably for 6,400 h at − 5 °C, 10,330 h at 25 °C, and 2,250 h at 40 °C, with a high DOD of 85.2%. 3 Achieves 99.59% Coulombic efficiency, suppresses dendrite growth, and maintains 150 mAh g−1 capacity after 1,750 cycles in NH4+-V2O5 full cells.